ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI TINDAKAN KECURANGAN (STUDI EMPIRIS PADA PERUSAHAAN SWASTA PERKEBUNAN KELAPA SAWIT DI RIAU) - Rahmat Syahputra Tarigan; Amir Hasan; Andreas Andreas (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This research was conducted by using survey method to palm oil plantation office in Riau region. This study aims to determine empirical evidence of the influence of compensation, internal control, organizational commitment and the competence of employees against fraud. The population in this research is 76 palm oil plantation office in Riau region. The sample is 171 respondents. The type of data used is primary data with data collection method using questionnaire.Data analysis method used in this research is multiple regression (multiple regression) with the help of software SPSS Version 24 for windows. The results showed that the value of compensation suit regression coefficient of -0.696, internal control 0.804, organizational commitment 0.361, kompentensi 0.353 significant effect on fraud with significance 0.002, 0001, 0001 and 0.000 and alpha <0.05. Adjusted R square value is equal to 0.473 which means equal to 47.3% independent variable in this research able to influence the dependent variable, while the rest equal to 52.7% explained by other variables.